2019
DOI: 10.1515/tw-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

Mobilitätsbedingte Klimawirkung einer alpinen Tourismusdestination

Abstract: ZusammenfassungAnhand von Befragungen in der Tiroler Gemeinde Alpbach wird untersucht, in wie weit sich das Bewusstsein für die Zusammenhänge zwischen Tourismus und Klimawandel bei Bewohnern, Beschäftigten und Gästen unterscheidet. Zudem wird eine Gesamtjahresbilanz der Mobilität von Gästen, Bewohnern und Beschäftigten und des damit verbundenen CO2-Ausstoßes dieser Gemeinde abgeschätzt. Zwar ist bei allen Gruppen ein grundsätzliches Problembewusstsein festzustellen und eine gewisse Bereitschaft für Maßnahmen z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…Car travel, due to its dominant role in Austrian tourism, heavily contributes to the sector's greenhouse gas emissions, both at the level of a single destination (Unger et al 2016), as well as for the entire country (Gühnemann et al 2021). Tourists appear to be well aware of their travel carbon footprint, yet are not willing to change their behavior substantially (Mailer et al 2019). Furthermore, traffic generated by tourists can even disrupt daily activities and travel patterns of local inhabitants, who experience severe difficulties in traveling due to lack of alternative roads in densely built-up and narrow mountain valleys.…”
Section: Introductionmentioning
confidence: 99%
“…Car travel, due to its dominant role in Austrian tourism, heavily contributes to the sector's greenhouse gas emissions, both at the level of a single destination (Unger et al 2016), as well as for the entire country (Gühnemann et al 2021). Tourists appear to be well aware of their travel carbon footprint, yet are not willing to change their behavior substantially (Mailer et al 2019). Furthermore, traffic generated by tourists can even disrupt daily activities and travel patterns of local inhabitants, who experience severe difficulties in traveling due to lack of alternative roads in densely built-up and narrow mountain valleys.…”
Section: Introductionmentioning
confidence: 99%
“…Although local travel is responsible for a considerably smaller part of the overall footprint of one's vacation trip (CO2 emissions, energy consumption, etc.) than the long-distance component (Peeters and Schouten, 2006;Patterson et al, 2007;Mailer et al, 2019), it is of capital importance for the choice of transport mode for the long-distance trip to the destination, as repeatedly highlighted in the literature (cf. Böhler et al, 2006;Rheinberger et al, 2007;Dolnicar et al, 2010;Bursa and Mailer, 2018), and thereby indirectly affects the environmental impact of the entire travel pattern of a tourist (as depicted in Fig.…”
Section: Theoretical Implicationsmentioning
confidence: 94%
“…However, this contradiction between the expectancy of more awareness (for which higher education might be a proxy) and choosing less environmentally friendly modes of transport was also observed for long-haul travelers by Böhler et al (2006) (2) denial mechanisms (referring to responsibility, external factors, e.g., financial and time constraints, or limited accessibility); (3) downward comparison (worse behavior happens), an exceptional situation (on holiday vs. at home), and covering harms with the benefits that tourism offers. Mailer et al (2019) found that tourists are still not ready to welcome dramatic changes that limit their freedom, accepting relatively easy or temporary compromises that enhance sustainability.…”
Section: Determinants Of Holiday Travel Behavior: Multivariate Analysismentioning
confidence: 99%